Stress and strain concentrations of completely overlapped tubular joints - Gao, Fei (2008)
The failure of offshore steel jackets is mainly due to fatigue at joint intersections of members. There are several methods available for fatigue design of tubular joints but the hot spot stress (HSS) approach is regarded as the most widely used method. This design method depends on the accurate prediction of stress concentration factor (SCF) for tubular joints under general load conditions. In the past, numerical and experimental works have extensively been carried out to study the SCF of simple tubular joints. Many SCF parametric equations have been developed and proposed for fatigue design of the joints. However, the recommendation for fatigue design of completely overlapped tubular joints is still insufficiently covered in the codes and guides.